A new hybrid model for the supplier selection decision. (4th March 2010) - Dominic, P.D.D.; Whab, Arif Abdel; Kannabiran, G.; Foong, Oi Mean
The decision-making process is a huge and crucial activity that must be given a high level of attention by decision makers and managers, as it affects all business strategies in organisations. As a result of the rapidly increasing and sustainable needs of organisations, suppliers have become essential to any business. Decision makers and managers face challenges when they are about to select suppliers, and the organisation will face more obstacles when a poor decision is made. This paper presents a new hybrid model which combines the linear weightage and Analytic Hierarchy Process (AHP) models for the supplier selection process. The new model can guarantee better decisions and provide a robust tool for assisting decision makers and managers to make the right decision and select the most suitable supplier. The proposed model was applied in a real-life case study and the 'what-if' analysis technique was used to assess the proposed model and its effectiveness.